Resolution based on the results of the III annual scientific and practical conference «Real clinical practice in a changing world. Challenges and Solutions» - A. S. Kolbin (Реальная клиническая практика: данные и доказательства, 2022)
On September 29, 2022, the Association of Specialists in Health Technology Assessment, the Association of Clinical Pharmacologists, the St. Petersburg branch of the International Society for Pharmacoeconomic Research and Scientific Analysis (ISPOR) organized and held the III annual scientific and practical conference with international participation «Real clinical practice in a changing world. Challenges and Solutions». The topic of the conference brought together leading Russian and world experts in the field of RWD/ RWE.